2009, No. 5, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Accounting theory and practice Deimantė Kviklienė, Application of Generally Accepted Accounting Principles in the Baltic States, 7 Kristina Rudžionienė, Changes of evaluation of financial statements‘ elements in Lithuanian accounting regulation of public sector, 15 Kristina Rudžionienė, Inga Pečeliūnienė, Evaluation methods of financial statements‘ elements in Lithuanian accounting regulation of public sector, 25 Kostas Valužis, Sąskaitų korespondencijų reikšmė ir netikslios teisės aktų formuluotės – žala valstybės ir jos piliečiams, 35 Auditing theory and practice Dalia Daujotaitė, Performance audit in the public sector: theoretical dimension, 47 Rasa Kanapickienė, Fraud risk management in process of internal control , 60 Training of accounting specialists Giedrė Balkytė, Milda Kvekšienė, Development of professional competencies of Accountancy and Finance study programmes students during the final internship, 67 Gintarė Jakštonytė, Lukas Giriūnas, Evaluation of influence of the accountant’s professional image and prestige on the selection of accounting specialization at universities, 74 Jadvyga Jurevičienė, Vilija Kolaitienė, The role of computerized accounting in the improvement of specialist training, 80 Auksė Makšeckienė, The role of practical work experience in the study process, 87 Romualdas Valkauskas, Training abilities of accounting specialists and economic statistics, 92 Accounting abroad Mindaugas Laurynaitis, Financial accounting regulation: German perspective, 99